Polish Captain Andrzej Okun’s Role in the Military Campaigns Against the Ukrainian Cossacks (1648 – beginning of the 50s of the ХVII century) - Потоцький, В'ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with the officer of Rzeczpospolita army Andrzej Okun’s biography and particularly focuses on his participation in the war against the Cossacks in Ukraine (1648-1657). The author managed to find out that Andrew Okun, could have been, was a veteran of the war of 1638 and also served in the rank of captain of the Crown army at least until February 1654. He fought against the Khmelnytsky’s rebels since June 1648. It is quite possible that he participated in the battle of Pyliavtsi and defended Lviv in October 1648. Also Okun as part of Andrzej Firleya’ troops fought in Volyn in 1649 and, obviously, he participated in the defense of Zbarazh. From 1650 to mid-1652 this Polish gentleman was in a Warsaw prison for the attack on the Moscow embassy. In February and March 1654 he led two assaults of the fortresses of Busha in Podillya. In May 1654 Okun was captured by the Cossacks and died from his wounds